2022
DOI: 10.3389/fvets.2022.887676
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Test of a New Endoprosthesis for Cylindrical Medullary Canals in Dogs

Abstract: Exo-endoprosthesis is a limb salvage procedure for animals, although only expensive metal devices have been described. Now-a-days, new materials for this type of implant could be considered due to novel and affordable manufacturing techniques. However, a factor of safety (FoS) should be considered. There are kinetic and kinematic studies of canine natural gaits, which can be used to establish an FoS for mechanical tests for new non-metallic devices. Polyetheretherketone (PEEK) is used in different specialties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Mechanical properties of the 3D-printed PEEK (Young’s modulus, tensile strength, and bending strength) had already been determined in a previous study [ 20 ]. To determine de Poisson’s ratio of the 3D-printed PEEK, an increasing load was applied with a Universal Testing Machine IBTH/500 (SAE Ibertest, Madrid, Spain) ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mechanical properties of the 3D-printed PEEK (Young’s modulus, tensile strength, and bending strength) had already been determined in a previous study [ 20 ]. To determine de Poisson’s ratio of the 3D-printed PEEK, an increasing load was applied with a Universal Testing Machine IBTH/500 (SAE Ibertest, Madrid, Spain) ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting alternative as a polymer is polyether ether ketone (PEEK) [ 19 ]. It is demonstrated that 3D-printing reduces mechanical properties of polymers, and PEEK is no exception [ 20 ]. Its mechanical properties, even if printed models had 100% infill, were inferior to those of injection-molded PEEK due to the porosity that remains after the 3D-printing process [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations